Sulfur-rich polymer and preparation method thereof, positive electrode material, positive electrode and lithium-sulfur battery

By injecting the sulfur element into a reverse vulcanization reaction with TVPA in a solution environment, the sulfur-rich polymer S-TVPA is prepared, which solves the problem of capacity attenuation caused by the "shuttle effect" of lithium sulfur batteries, and achieves higher cycling performance and simpler preparation process.

CN119517983APending Publication Date: 2025-02-25JIANGSU PYLON BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411740091.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The "shuttle effect" of lithium-sulfur batteries leads to rapid attenuation of capacity. The existing methods of preparing sulfur-rich polymers in reverse vulcanization have problems such as uneven reactions, cumbersome preparation steps and high energy consumption.

Method used

The sulfur element is reverse vulcanized with TVPA in a solution environment, and cross-linking polymerization obtains the sulfur-rich polymer S-TVPA. TVPA molecules introduce electron-rich active sites into the organic framework to effectively adsorb lithium polysulfide intermediates and alleviate the "shuttle effect".

Benefits of technology

The sulfur-rich polymer prepared by this method can effectively alleviate the capacity attenuation of lithium-sulfur batteries, improve cycle performance, simplify the preparation process, and reduce energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517983A_ABST
    Figure CN119517983A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, and discloses a sulfur-rich polymer and a preparation method thereof, a positive electrode material, a positive electrode and a lithium-sulfur battery. The preparation method of the sulfur-rich polymer comprises the following steps: carrying out reverse vulcanization reaction on elemental sulfur and TVPA in a solution environment, and carrying out cross-linking polymerization to obtain the sulfur-rich polymer S-TVPA; and the structural formula of the TVPA is # imgabs0 #. According to the preparation method disclosed by the invention, compared with reverse vulcanization by melting powdered sulfur, the subsequent reaction process can be carried out more mildly, and implosion is avoided; after the reaction is finished, a powder product can be prepared and can be directly applied to the lithium-sulfur battery. The prepared sulfur-rich polymer has better electrochemical performance when being applied to a lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a sulfur-rich polymer and a preparation method thereof, a positive electrode material, a positive electrode and a lithium-sulfur battery. Background Art

[0002] At present, lithium-ion batteries, as a new type of clean energy, have been widely used in all walks of life. However, they still have the bottleneck of low energy density. As a branch of lithium-ion batteries, lithium-sulfur batteries have a theoretical energy density of up to 2600 Wh / kg, which has obvious advantages over conventional lithium-ion batteries. Among them, sulfur, as the positive electrode material of lithium-sulfur batteries, has a theoretical gram capacity of up to 1675 mAh / g. However, pure sulfur powder has obvious disadvantages as a positive electrode active material, namely the "shuttle effect" of lithium-sulfur batteries. This effect is mainly attributed to the fact that the lithium polysulfide intermediates produced when lithium and sulfur undergo electrochemical reactions can be dissolved in ether electrolytes. Due to the concentration gradient effect, lithium polysulfide will diffuse to the negative electrode and eventually be reduced at the negative electrode to form inactivated sulfur, which ultimately leads to the rapid attenuation of the capacity of lithium-sulfur batteries. Therefore, the functional design of sulfur-based positive electrode materials is particularly important.

[0003] The sulfur-containing polymer prepared by the reverse vulcanization (reverse vulcanization) method is a potential positive electrode material for lithium-sulfur batteries. The organic skeleton it contains can effectively physically and chemically adsorb lithium polysulfide through functional design, thereby achieving the function of alleviating the "shuttle effect". At present, the conventional reverse vulcanization method is to directly heat and melt the sulfur powder, then add the unsaturated cross-linking agent to the molten sulfur and directly react at high temperature to form a precursor, and then solidify the precursor at high temperature for a long time to form a sulfur-containing polymer solid. In order to apply it to lithium-sulfur batteries, it is necessary to perform long-term ball milling to reach micron-level size. This method has certain disadvantages. First, the molten sulfur and the cross-linking agent are directly reacted at high temperature, and there is a probability that the reaction will be locally uneven, which will lead to the "auto-acceleration" phenomenon of the polymerization reaction, and finally violent polymerization occurs, and the experiment fails. In addition, the precursor is a viscous liquid, and it is also necessary to perform long-term high-temperature curing (generally more than 12 hours) and subsequent long-term ball milling (generally more than 4 hours). The preparation steps are cumbersome and energy consumption is high.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The object of the present invention is to provide a sulfur-rich polymer and a preparation method thereof, a positive electrode material, a positive electrode and a lithium-sulfur battery, aiming to improve at least one problem mentioned in the background technology.

[0006] The present invention is achieved in that: In a first aspect, the present invention provides a method for preparing a sulfur-rich polymer, comprising: The sulfur element and TVPA are subjected to reverse vulcanization reaction in a solution environment, and the sulfur-rich polymer S-TVPA is obtained by cross-linking polymerization; The structural formula of TVPA is: .

[0007] In an optional embodiment, the method of inverse sulfide reaction between elemental sulfur and TVPA in a solution environment includes: Mixing a reaction solution containing sulfur element with TVPA, wherein the solvent of the reaction solution is a non-polar solvent; After mixing, fully react in an inert atmosphere at 135~150℃; Optionally, the non-polar solvent is selected from at least one of n-hexane and carbon tetrachloride.

[0008] In an optional embodiment, the entire reaction process is carried out under stirring; Optionally, the inert atmosphere is a nitrogen atmosphere or an argon atmosphere; Optionally, the reaction time is 8 to 12 hours.

[0009] In an optional embodiment, the mass ratio of elemental sulfur to TVPA is 1 to 5:1; Optionally, the concentration of elemental sulfur in the reaction solution is 3-15 g / L.

[0010] In an optional embodiment, before the reaction solution is mixed with TVPA for reaction, the step further includes obtaining the reaction solution, and the method for obtaining the reaction solution includes: After the sulfur powder and the solvent are mixed and stirred evenly, the temperature of the mixed system is increased to 135-150° C. and stirring is continued until the sulfur powder is completely dissolved to obtain a reaction solution.

[0011] In an optional embodiment, after the reverse sulfidation reaction is completed, a mixed solution is obtained, and the mixed solution comprises: The mixed liquid is subjected to solid-liquid separation, and then the obtained solid is washed and vacuum-dried to obtain the S-TVPA; Optionally, the solid-liquid separation method is suction filtration; Optionally, the washing method includes first washing with ethanol and then washing with deionized water.

[0012] In a second aspect, the present invention provides a sulfur-rich polymer prepared by the preparation method of any one of the aforementioned embodiments.

[0013] In a third aspect, the present invention provides a positive electrode material, comprising the sulfur-rich polymer according to the aforementioned embodiment.

[0014] In a fourth aspect, the present invention provides a positive electrode, the active component of which includes the sulfur-rich polymer according to the aforementioned embodiment.

[0015] In a fifth aspect, the present invention provides a lithium-sulfur battery, comprising a positive electrode as described in the aforementioned embodiment.

[0016] The present invention has the following beneficial effects: 1. Sulfur and TVPA are cross-linked to form a new sulfur-rich polymer. TVPA molecules can introduce electron-rich active sites (mainly from lone pairs of electrons on N atoms) into the organic skeleton of the sulfur-rich polymer, which can effectively chemically adsorb the relatively electron-poor lithium in the lithium polysulfide intermediate during the lithium-sulfur electrochemical reaction, thereby alleviating the dissolution of lithium polysulfide in ether-based electrolytes, weakening the influence of the "shuttle effect", reducing the single-cycle capacity decay rate of lithium-sulfur batteries, and improving their cycle performance.

[0017] 2. Sulfur and TVPA undergo reverse sulfurization in a solution environment. Compared with melting sulfur powder for reverse sulfurization, this can make the subsequent reaction process more gentle and prevent sudden polymerization. After the reaction, a powder product can be obtained, which can be directly used in lithium-sulfur batteries without the need for ball milling. The preparation process is simple and has low energy consumption. BRIEF DESCRIPTION OF THE DRAWINGS In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0018] Figure 1 Schematic diagram of the reaction principle; Figure 2 is a schematic diagram of the reaction device; Figure 3 This is a SEM image of the S-TVPA prepared in Example 1; Figure 4 The cyclic voltammetry test data of the S-TVPA prepared in Example 1 after being charged; Figure 5 The figure is a comparison chart of the cycle performance after power-off of the S-TVPA prepared in Example 1 and the sulfur powder in the control group. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0020] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0021] An embodiment of the present invention provides a method for preparing a sulfur-rich polymer, comprising: The sulfur element and TVPA are subjected to reverse vulcanization reaction in a solution environment, and the sulfur-rich polymer S-TVPA is obtained by cross-linking polymerization; The structural formula of TVPA is: .

[0022] The method for preparing the sulfur-rich polymer provided by the present invention is as follows: Figure 1 As shown, a new sulfur-rich polymer is obtained by cross-linking and polymerization of sulfur and TVPA in a solution environment by the reverse vulcanization method. TVPA molecules can introduce electron-rich active sites (mainly derived from lone pairs of electrons on N atoms) into the organic skeleton of the sulfur-rich polymer, which can effectively chemically adsorb the relatively electron-poor lithium in the lithium polysulfide intermediate during the lithium-sulfur electrochemical reaction, thereby alleviating the dissolution of lithium polysulfide in ether-based electrolytes, weakening the influence of the "shuttle effect", reducing the single-cycle capacity decay rate of lithium-sulfur batteries, and improving their cycle performance.

[0023] The preparation method provided by the present invention is to react sulfur and TVPA in a solvent environment, and has two advantages: 1. It can make the subsequent reverse sulfurization reaction process proceed more gently; 2. After the reaction is completed, a powder product can be obtained, which can be directly used in lithium-sulfur batteries.

[0024] Therefore, the sulfur-rich polymer prepared by the preparation method provided by the present invention can be used as a positive electrode active material in a lithium-sulfur battery, and can enable the lithium-sulfur battery to have better electrochemical performance.

[0025] The preparation method is specifically as follows: S1. Preparation of reaction solution Sulfur powder and solvent are placed in a container, an inert gas is introduced into the container for protection, and the mixture is stirred and dispersed evenly. Then, the temperature of the mixed system is increased and stirred to completely dissolve the sulfur powder in the solvent to obtain a reaction solution.

[0026] Preferably, the solvent is a non-polar solvent, which can dissolve sulfur, thereby achieving a reaction between sulfur and TVPA in a solution environment.

[0027] Optionally, the non-polar solvent is selected from at least one of n-hexane and carbon tetrachloride.

[0028] Optionally, the amount of solvent used is sufficient to dissolve the sulfur powder. Preferably, to ensure a more suitable reaction rate and produce a powder product with better particle size, the ratio of sulfur powder to solvent is 0.45-2.25 g:150 mL, that is, the concentration of sulfur in the reaction solution is 3-15 g / L (e.g., 3 g / L, 5 g / L, 8 g / L, 10 g / L, 13 g / L or 15 g / L), preferably 13.33 g / L.

[0029] Optionally, the temperature of the mixed system is increased to 135-150°C (eg, 135°C, 140°C, 145°C, or 150°C).

[0030] Optionally, the inert gas is nitrogen or argon.

[0031] S2. Mixed reaction Still under the protection of inert gas, TVPA is added to the high temperature (135-150°C) reaction solution, and stirring is continued. The system temperature is controlled to be 135-150°C (e.g., 135°C, 140°C, 145°C or 150°C) to allow TVPA to fully react with S to obtain a light brown solid powder suspended in the solution.

[0032] Optionally, to obtain S-TVPA with better performance, the mass ratio of sulfur to TVPA in the reaction solution is 1 to 5:1 (e.g., 1:1, 2:1, 3:1, 4:1 or 5:1), and the preferred ratio is 4:1.

[0033] Optionally, the time to achieve sufficient reaction is 8 to 12 h (eg, 8 h, 10 h or 12 h).

[0034] S3. Extraction product The mixed system after the reaction in step S2 is filtered to obtain a solid substance, which is washed with ethanol and deionized water in sequence, and then dried to obtain an S-TVPA product.

[0035] An embodiment of the present invention provides a sulfur-rich polymer, which is prepared by the preparation method provided by the embodiment of the present invention.

[0036] An embodiment of the present invention provides a positive electrode material, including the sulfur-rich polymer provided by an embodiment of the present invention.

[0037] An embodiment of the present invention provides a positive electrode, the active component of which includes the sulfur-rich polymer provided by the embodiment of the present invention.

[0038] Specifically, the preparation method of the positive electrode includes: S-TVPA, conductive agent and binder are ground and mixed in appropriate mass ratios, and the ground mixed powder is evenly dispersed in NMP solvent to make slurry. The slurry is then evenly coated on the surface of aluminum foil and then placed in a vacuum drying oven for drying. After drying, the positive electrode sheet is obtained by cutting.

[0039] An embodiment of the present invention provides a lithium-sulfur battery, including the positive electrode provided by the embodiment of the present invention.

[0040] Optionally, the electrolyte of the lithium-sulfur battery is an ether-based electrolyte. The specific formula is, for example, 1.0 M LiTFSI as lithium salt, 1:1 volume mixture of DME: DOL as solvent, and 1% LiNO3 as additive.

[0041] Example 1 like Figure 2 As shown, first, 2 g of sulfur powder and 150 mL of n-hexane were added to a 250 mL three-necked round-bottom flask, nitrogen was introduced for atmosphere protection, and a magnet and a magnetic stirrer were used for slow stirring and dispersion (rotation speed 300 rpm).

[0042] Add a condenser device, raise the solution temperature to 135°C, and stir at an increased speed (600 rpm) for about 30 minutes at 135°C. At this time, it can be observed that the sulfur powder has dissolved in the n-hexane, and there is no obvious powdery object in the flask.

[0043] 0.5g TVPA was added to the solution and reacted continuously for 10 hours at 135℃ nitrogen atmosphere and 600rpm rotation speed to obtain a light brown solid powder suspended in the solution. The suspension was filtered to obtain a solid powder, which was washed with alcohol and deionized water in turn, and finally dried under vacuum at room temperature for 24 hours to obtain the final product, S-TVPA sulfur-rich polymer. The scanning electron microscope (SEM) photo of the product is shown in the figure. Figure 2 As shown, from Figure 3 It can be seen that the particle morphology is approximately spherical, the size is about 10 μm, and there is no obvious particle agglomeration phenomenon.

[0044] Example 2 This embodiment is substantially the same as embodiment 1, except that the amount of sulfur powder used is 2 g, and the amount of TVPA used is 2 g.

[0045] Example 3 This embodiment is substantially the same as embodiment 1, except that the amount of sulfur powder used is 2 g, and the amount of TVPA used is 0.4 g.

[0046] Example 4 This embodiment is basically the same as embodiment 1, except that carbon tetrachloride is used as the solvent, the dissolution temperature of sulfur powder is 150° C., the reaction temperature is 150° C., and the reaction time is 8 h.

[0047] Experimental example The products obtained in each embodiment were made into pole pieces and assembled into batteries, and their performance was tested. The details are as follows: a. Grind and mix the S-TVPA, carbon black conductive agent and PVDF binder prepared in each embodiment at a mass ratio of 8:1:1, and evenly disperse the ground mixed powder in NMP solvent to make slurry (1 g of mixed powder is added with 3 ml of NMP). Then evenly coat the slurry on the surface of aluminum foil, and then put it in a vacuum drying oven to dry at 60°C. After drying, cut it to obtain the positive electrode sheet.

[0048] The positive electrode sheet was made by using sulfur powder as the positive electrode active material, and its preparation process was consistent with the above, which served as the control group.

[0049] b. Assemble the positive electrode sheet, separator, lithium sheet and electrolyte (formula: lithium salt is 1.0 M LiTFSI, solvent is DME:DOL = 1:1 volume mixture, additive is 1% LiNO3) into a CR2025 button battery.

[0050] The electrochemical performance test of the buckle is divided into room temperature cyclic voltammetry curve test and room temperature cycle test. The specific test method of room temperature cyclic voltammetry curve is to set the voltage range to 1.5-3.0 V vs Li at 25 degrees. + / Li, the voltage sweep rate is 0.1mV / s, and the cycle is repeated 3 times to obtain a stable curve, and the current density is calculated using the sulfur mass of the positive electrode. The specific test method for room temperature cycling is to place the battery under 25 degrees for 18 hours, and then perform a 0.2C (1C = 1672 mAh / g) constant current charge and discharge cycle test in the range of 1.5-2.8 V, record the battery capacity, and then calculate the specific capacity using the sulfur mass of the positive electrode. The test results are as follows Figure 4 , Figure 5 And as shown in Table 1.

[0051] Figure 4 The cyclic voltammetry test data of the S-TVPA sulfur-containing polymer prepared in Example 1 shows that the S-TVPA sample has two reduction peaks in the range of 2.30-2.35 V and 1.99-2.04 V, which are respectively attributed to the long-chain soluble polysulfides (mainly S6 2- and S4 2-) and the formation of short-chain insoluble polysulfides (Li2S2 and Li2S), which is basically consistent with sulfur powder. Correspondingly, two oxidation peaks attributed to the oxidation of Li2S2 and Li2S can be observed at 2.28–2.45 V. Figure 5 The figure is a comparison of the cycling performance of the S-TVPA sulfur-containing polymer obtained in Example 1 and the control group at 0.2C. The data show that the initial gram capacity of S-TVPA at 0.2C is 823 mAh / g, and the capacity decay rate per cycle is 0.167%, which is much better than the initial gram capacity of sulfur powder at 0.2C of 691 mAh / g and the capacity decay rate per cycle of 0.310%.

[0052] Table 1 Test data of each embodiment and control group

[0053] It can be seen from the data in Table 1 that the 0.2C initial gram capacity and the capacity decay rate per cycle obtained in each embodiment are significantly better than those of the control group, indicating that the S-TVPA prepared by the preparation method provided in the embodiment of the present invention has significantly better performance as a positive electrode active material than sulfur powder.

[0054] In summary, the preparation method provided by the embodiment of the present invention has the following advantages: 1. Sulfur and TVPA are cross-linked to form a new sulfur-rich polymer. TVPA molecules can introduce electron-rich active sites (mainly from lone pairs of electrons on N atoms) into the organic skeleton of the sulfur-rich polymer, which can effectively chemically adsorb the relatively electron-poor lithium in the lithium polysulfide intermediate during the lithium-sulfur electrochemical reaction, thereby alleviating the dissolution of lithium polysulfide in ether-based electrolytes, weakening the influence of the "shuttle effect", reducing the single-cycle attenuation rate of the specific capacity of lithium-sulfur batteries, and improving their cycle performance.

[0055] 2. Sulfur and TVPA undergo reverse sulfurization in a solution environment. Compared with melting sulfur powder for reverse sulfurization, this can make the subsequent reaction process more gentle and prevent sudden polymerization. After the reaction, a powder product can be obtained, which can be directly used in lithium-sulfur batteries without the need for ball milling. The preparation process is simple and has low energy consumption. The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a sulfur-rich polymer, characterized in that: include: The sulfur element and TVPA are subjected to reverse vulcanization reaction in a solution environment, and the sulfur-rich polymer S-TVPA is obtained by cross-linking polymerization; The structural formula of TVPA is: .

2. The preparation method according to claim 1, characterized in that: Methods for inverse sulfide reaction between sulfur and TVPA in a solution environment include: Mixing a reaction solution containing sulfur with TVPA, wherein the solvent of the reaction solution is a non-polar solvent; After mixing, fully react in an inert atmosphere at 135~150℃; Optionally, the non-polar solvent is selected from at least one of n-hexane and carbon tetrachloride; Optionally, the concentration of elemental sulfur in the reaction solution is 3-15 g / L.

3. The preparation method according to claim 2, characterized in that: The entire reaction process is carried out under stirring; Optionally, the inert atmosphere is a nitrogen atmosphere or an argon atmosphere; Optionally, the reaction time is 8 to 12 hours.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the sulfur element to the TVPA is 1-5:

1.

5. The preparation method according to claim 2, characterized in that: Before the reaction solution is mixed with TVPA for reaction, the method further includes obtaining the reaction solution, and the method of obtaining the reaction solution includes: After the sulfur powder and the solvent are mixed and stirred uniformly, the temperature of the mixed system is increased to 135-150° C. and the stirring is continued until the sulfur powder is completely dissolved to obtain the reaction solution.

6. The preparation method according to claim 1, characterized in that: After the reverse sulfidation reaction is completed, a mixed solution is obtained, which comprises: The mixed liquid is subjected to solid-liquid separation, and then the obtained solid is washed and vacuum-dried to obtain the S-TVPA; Optionally, the solid-liquid separation method is suction filtration; Optionally, the washing method includes first washing with ethanol and then washing with deionized water.

7. A sulfur-rich polymer, characterized in that The method is prepared according to any one of claims 1 to 6.

8. A positive electrode material, characterized in that Comprising the sulfur-rich polymer as described in claim 7.

9. A positive electrode, characterized in that The active component thereof comprises the sulfur-rich polymer as claimed in claim 7.

10. A lithium-sulfur battery, characterized in that: Comprising the positive electrode as claimed in claim 9.